Moon Ingress to Zodiac on Soybean and Corn Price Movement and Their Impact on Feed Stock Prices - Suhartono suhartono; Syamsu Alam; Muhammad Toaha (Magister Management, Hasanuddin University, 2022)
The use of astrology in capital market analysis is controversial, despite the many claims through the publication of scientific articles about its effectiveness in the stock market. This study aims to examine the relationship between moon ingress to zodiac with the price of raw material for feed, soybean meal, corn, and stock price movements of feed on the Indonesia Stock Exchange. The design used in this research is a descriptive and explanatory method. The population in this study is 260 daily data on ingress data, corn prices, soybean meal prices, and company stock prices from feed sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique in this study uses the saturated sample technique. Data analysis technique using chi-square. The results of this study indicate that there is a significant relationship between moon ingress to zodiac with the prices of raw materials for feed, soybean meal, and corn and the movement of stock prices for feed on the Indonesia Stock Exchange.